PENGARUH NPF, BOPO, GDP DAN SBIS TERHADAP PERTUMBUHAN ASET PERBANKAN SYARIAH DI INDONESIA - Nadhiera Ahya Dhiba; Lavlimatria Esya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This study aims to analyze the factors that influence the growth of Islamic banking assets in Indonesia in the short and long term. This study uses monthly secondary data from 2012 to 2016. The analytical model used is the Error Correction Model (ECM). The advantages of this model can explain short-term and long-term behavior. The results showed the Non-Performing Financing (NPF) variable in the short term had a negative and significant relationship while in the long run it had a negative and not significant relationship to the growth of Islamic banking assets in Indonesia. The Gross Domestic Product (GDP) variable in the short and long term has a positive and not significant relationship to the growth of Islamic banking assets in Indonesia. Operating Cost Variable to Operating Income (BOPO) in the short and long term has a positive and not significant relationship to the growth of Islamic banking assets in Indonesia. Indonesian Islamic Bank Certificate Variables (SBIS) in the short term have a positive and significant relationship while in the long run have a positive and not significant relationship to the growth of Islamic banking assets in Indonesia.